Fire blight QTL analysis in a multi-family apple population identifies a reduced-susceptibility allele in 'Honeycrisp'. (1st February 2021) - Kostick, Sarah A; Teh, Soon Li; Norelli, John L; Vanderzande, Stijn; Peace, Cameron; Evans, Kate M
Abstract: Breeding apple cultivars with resistance offers a potential solution to fire blight, a damaging bacterial disease caused by Erwinia amylovora . Most resistance alleles at quantitative trait loci (QTLs) were previously characterized in diverse Malus germplasm with poor fruit quality, which reduces breeding utility. This study utilized a pedigree-based QTL analysis approach to elucidate the genetic basis of resistance/susceptibility to fire blight from multiple genetic sources in germplasm relevant to U.S. apple breeding programs. Twenty-seven important breeding parents (IBPs) were represented by 314 offspring from 32 full-sib families, with 'Honeycrisp' being the most highly represented IBP. Analyzing resistance/susceptibility data from a two-year replicated field inoculation study and previously curated genome-wide single nucleotide polymorphism data, QTLs were consistently mapped on chromosomes (Chrs.) 6, 7, and 15. These QTLs together explained 28% of phenotypic variation. The Chr. 6 and Chr. 15 QTLs colocalized with previously reported QTLs, while the Chr. 7 QTL is possibly novel. 'Honeycrisp' inherited a rare reduced-susceptibility allele at the Chr. 6 QTL from its grandparent 'Frostbite'. The highly resistant IBP 'Enterprise' had at least one putative reduced-susceptibility allele at all three QTLs. In general, lower susceptibility was observed for individuals with higher numbers of reduced-susceptibility alleles across QTLs. This study highlighted QTL mapping and allele characterization of resistance/susceptibility to fire blight in complex pedigree-connected apple breeding germplasm. Knowledge gained will enable more informed parental selection and development of trait-predictive DNA tests for pyramiding favorable alleles and selection of superior apple cultivars with resistance to fire blight.